2020
DOI: 10.1111/jhn.12837
|View full text |Cite
|
Sign up to set email alerts
|

Association of iodine‐related knowledge, attitudes and behaviours with urinary iodine excretion in pregnant women with mild iodine deficiency

Abstract: Background: China's universal salt-iodization program has all but eliminated iodine de ciency disorders. Concern has shifted to mild iodine de ciency. Our study examined factors with the potential to predict mild iodine de ciency in pregnant women. Methods: A total of 2 400 pregnant women were enrolled using a multistage, strati ed, random-sampling method. Data were collected through face-to-face interviews, a standardized questionnaire, an iodine-related knowledge questionnaire, urine samples, and household c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
(47 reference statements)
2
16
0
Order By: Relevance
“…727 pregnant women were enrolled as the test cohort. The regional iodine status of pregnant women in Shanghai is considered adequate during the first trimester [urinary iodine concentration (UIC), 155.0 μg/L] and second trimester (UIC, 151.0 μg/L) ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…727 pregnant women were enrolled as the test cohort. The regional iodine status of pregnant women in Shanghai is considered adequate during the first trimester [urinary iodine concentration (UIC), 155.0 μg/L] and second trimester (UIC, 151.0 μg/L) ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…24 As a result of the high within-person variability of a single spot urine, WHO has limited the use and interpretation based on single spot urine per participant to the population median of a sufficiently large group (in general, >30). 10 In the present study, the sampling error (95% confidence interval or confidence interval [CI] of median UIC) was considered and calculated using bootstrapping. Pregnant women were divided into 80 units according to the district.…”
Section: Urine Sample Collection Testing and Evaluationmentioning
confidence: 99%
“…Even though the iodine nutritional status of the population is adequate, pregnant women have mild iodine deficiency. 10,11 Dietary protein intake is closely related to thyroid function. Thyroxin is composed of amino acid derivatives, 12 and protein depletion decreases the responsiveness of animals to the catabolic functions of the thyroid.…”
Section: Introductionmentioning
confidence: 99%
“…As the high within-person variability of a single spot urine, the WHO has limited the use and interpretation based on single spot urine per participant to the population median of a su ciently large group (in general, > 30) [8]. In our study, the sampling error (95% con dence interval (CI) of the MUIC) was considered and calculated using bootstrapping.…”
Section: Data Collection and Diet Evaluationmentioning
confidence: 99%
“…Shanghai, which is the largest coastal city in China, has implemented the compulsory universal salt iodization since 1996. Even though the iodine nutritional status of the population is adequate, pregnant women are at risk for mild iodine de ciency [8,9]. A study in endemic zone of a sub-Himalayan region reported that a negative correlation was observed between urinary iodine concentration (UIC) and anti-TPO Ab [10].…”
Section: Introductionmentioning
confidence: 99%